Edutainment Module based on Local Culture of Eastern Pantai Utara, Central Java Reviewed From Experts - Wanabuliandari, Savitri; Dwi Ardianti, Sekar; Saptono, Sigit; Alimah, Siti; Kurniasih, Nuning (International Journal of Engineering and Technology, 2018)
This research aims to determine (1) feasibility evaluation of the module, and (2) advice from the experts toward the module. The type of the study used is Research and Development by using the modified design from Borg and Gall. The stages done in this research include planning, development, and evaluation. In the planning stage, the researcher did the product validation activity by experts including material expert, language expert, and learning expert. The result of the research shows (1) the feasibility of the module according to the experts is in the very feasible category and (2) the material expert suggests to add explanations in the material sources used in the module, question examples, glossary, and integrity among contents, while the language expert suggests to give picture illustration according to the material, fix front cover, avoid words with double meanings, and use simple sentences, the learning expert suggests to make the integrity among the elements clearer and present the materials systematically and coherently. The suggestions from the three experts were then used to improve the edutainment module based on the local culture of eastern Pantai Utara (North Beach ) , Central Java, Indonesia.Â Â